Potensi buah delima (punica granatum) sebagai terapi adjuvan preeklampsia: A scoping review - Wahyuni, Endang Sri; Firrahmawati, Lely; Mahmudah, Irvina Nurul; Handayani, Juleha Duwi (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Preeclampsia is a leading cause of maternal mortality and a global health problem. Preeclampsia can be triggered by increased free radicals, which cause oxidative stress, endothelial dysfunction, and other organ damage. However, to date, no therapy has been proven to prevent preeclampsia other than pregnancy termination. A scoping review is needed to gather evidence related to the use of pomegranate and its derivatives for preeclampsia therapy as a basis for further basic and applied research. Purpose: To identify, evaluate, and summarize previous research evidence on the potential of pomegranate as an adjuvant therapy for preeclampsia. Method: A systematic review of literature published between January 2014 and June 2024 was conducted using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Articles were searched through Scopus, Sciencedirect, Proquest, and PubMed databases. The search used the keywords